Pengembangan Rencana Pembelajaran Mendalam (RPM) Matematika untuk Meningkatkan Pemahaman Konsep Peserta Didik - Oktavina, Vebri; Majid, Majid; Arifin, Irvin Novita; Ardini, Pupung Puspa; Abdullah, Gamar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop and examine the effectiveness of a Deep learning-Based Mathematics Lesson Plan (RPM) for fourth-grade students at SDIT Madani Luwuk Banggai Regency, Central Sulawesi. The research employed a Research and Development (R&D) method consisting of needs analysis, design, development, expert validation, and effectiveness testing stages. The research subjects were fourth-grade students divided into experimental and control groups. Data were collected through observations, interviews, documentation, and pretest–posttest assessments. Data analysis was conducted using descriptive statistics and the Wilcoxon Signed Rank Test as a non-parametric analysis. Expert validation results indicated that the developed RPM was categorized as highly feasible, with an average score of 91.11%. The effectiveness test results showed a significant improvement in students’ mathematics learning outcomes after the implementation of RPM, particularly in conceptual understanding and contextual application. It can be concluded that the mathematics RPM is effective as a learning plan to enhance both the learning process and mathematics achievement at the elementary school level. Keywords: Deep learning, Mathematics Lesson Plan, Elementary School, Research And Development